2022
DOI: 10.3389/fpsyg.2022.916449
|View full text |Cite
|
Sign up to set email alerts
|

Online learning satisfaction and its associated factors among international students in China

Abstract: The outbreak of the COVID-19 pandemic has caused a substantial transition of Chinese international education to online learning. This article discusses the impact of online learning from international students’ perspectives. Data were collected from exploratory interviews with a small group of international students at a research university and a nationwide survey involving 1,010 international students at 41 universities in China. A synthesis of the two studies’ findings pointed to low levels of online learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
2
7
1
Order By: Relevance
“…In contrast, this study revealed that the factors previously deemed as influentialsuch as the accessibility of online learning resources, course organization, and learning achievement-did not significantly influence student satisfaction [33,36]. In particular, the presence or absence of student interactions did not significantly affect satisfaction in the configurations of S1 and S2 despite its previously reported importance in online learning [32,33].…”
Section: Rq2: Combination Of Teacher Support and Student Engagement L...contrasting
confidence: 80%
See 2 more Smart Citations
“…In contrast, this study revealed that the factors previously deemed as influentialsuch as the accessibility of online learning resources, course organization, and learning achievement-did not significantly influence student satisfaction [33,36]. In particular, the presence or absence of student interactions did not significantly affect satisfaction in the configurations of S1 and S2 despite its previously reported importance in online learning [32,33].…”
Section: Rq2: Combination Of Teacher Support and Student Engagement L...contrasting
confidence: 80%
“…This study performed descriptive statistical analysis, and the results show that the mean score of student satisfaction was 3.73, between "neutral" (3) and "agree" (4), indicating that the participants tended to feel satisfied with their online CFL learning. This finding was largely consistent with the previous studies on online EFL learning [12,33,35] but different from reports of lower levels of satisfaction in studies on general online learning experiences among domestic students [15,26] and international students in Chinese HEIs during the pandemic [36]. Therefore, further research is needed to explore whether differences exist between international students' satisfaction with online CFL learning and their satisfaction with learning in their major fields of study and why.…”
Section: Rq1: Characteristics Of International Students' Satisfaction...supporting
confidence: 75%
See 1 more Smart Citation
“…Data analytics and machine learning algorithms play an important role in studying students' adaptation to online education systems. Data analytics can help to collect and process a large amount of data on student behaviour, feedback and performance, from which potential patterns and trends can be mined [6]. Through data analysis, it is possible to build an understanding of the complex relationships between the factors that influence students' adaptation to the online education system.…”
Section: Introductionmentioning
confidence: 99%
“…The level of student satisfaction is at an average score of 3.45 denote neutral which is related to stimulation and attractiveness (Agyeiwaah et al, 2022). Satisfaction of students from Africa is at a low level which is the result of low emotional engagement (Tian & Lu, 2022). Student satisfaction with online learning is related to online student attributes, time management, technical competencies, and online communication competencies (Rafsanjani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%